PENGARUH RETORIKA SALES MARKETING INVESTASI EMAS BANK SYARIAH TERHADAP MINAT BERINVESTASI MAHASISWA UNIVERSITAS MUHAMMADIYAH LAMPUNG: THE INFLUENCE OF SALES MARKETING RHETORIC OF SYARIAH BANK GOLD INVESTMENT ON THE INVESTMENT INTEREST OF STUDENTS OF MUHAMMADIYAH UNIVERSITY OF LAMPUNG - Eva Intan Komalasari, Murni Lestari; Noorikha Pandayahesti Saputeri; Warsiyah; Eki Tiyas Nurulia (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
Gold investment is one of the popular investments and is widely offered today, because the value of gold is stable and zero inflation, and the price of gold tends to increase. Islamic banks are one of the providers of gold investment programs with an installment system using the murabahah contract (buy and sell), but there are still many people including Generation Z who do not believe that gold investment in Islamic banks does not contain usury elements, so sales marketing who work in the sales sector must have good rhetoric so that the information can be conveyed and can be trusted. The purpose of this study is to determine how the rhetoric of sales marketing of Islamic bank gold investment affects the investment interest of students at the University of Muhammadiyah Lampung. The approach in this study is quantitative descriptive and verification, data is obtained through the distribution of questionnaires targeted at students at the University of Muhammadiyah Lampung who have received information about gold investment in Islamic banks, and to process the data the tool used is SPSS version. The results of this study indicate that there is an influence of 64.5% of the rhetoric variable (X) on the interest variable (Y), as well as the results of the t-test also state that the rhetoric variable has a simultaneous (significant) influence on the interest variable, and it can be concluded that Ha is accepted and H0 is rejected or there is an influence of the rhetoric variable (X) on the interest variable (Y), meaning that the rhetoric of sales marketing of Islamic bank gold investment is one of the things that influence the investment interest of students at the University of Muhammadiyah Lampung.